Alternative designs for clinical trials in rare diseases. Issue 4 (14th November 2016) - Abrahamyan, Lusine; Feldman, Brian M.; Tomlinson, George; Faughnan, Marie E.; Johnson, Sindhu R.; Diamond, Ivan R.; Gupta, Samir
Abstract : Evidence‐based medicine requires strong scientific evidence upon which to base treatment. In rare diseases, study populations are often small, and thus this evidence is difficult to accrue. Investigators, though, should be creative and develop a flexible toolkit of methods to deal with the problems inherent in the study of rare disease. This narrative review presents alternative clinical trial designs for studying treatments of rare diseases, including cross‐over and n‐of‐1 trials, randomized placebo‐phase design, enriched enrollment, randomized withdrawal design, and classes of adaptive designs. Examples of applications of these designs are presented along with their advantages and disadvantages. Additional analytical considerations such as Bayesian analysis, internal pilots, and use of biomarkers as surrogate outcomes are further discussed. A framework for selecting appropriate clinical trial design is proposed to guide investigators in the process of selecting alternative designs for rare diseases. © 2016 Wiley Periodicals, Inc.